A randomized, double-blind, placebo-controlled phase I trial of inhalation treatment of recombinant TFF2-IFN protein: A multifunctional candidate for the treatment of COVID-19 - Liu, Yan; Zhai, Guanxing; Fu, Weihui; Zhang, Xiaoyan; Xu, Jianqing (Frontiers in Pharmacology, 2022)
Background and Objectives: Coronavirus disease 2019 (COVID-19) has caused global pandemics in the last 3 years, and the development of new therapeutics is urgently needed. This study aimed to assess the safety, tolerated, and prolonged retention of recombinant protein trefoil factor 2 (TFF2)- interferon (IFN) in the respiratory tract of healthy volunteers. Methods: We conducted a randomized, double-blind, placebo-controlled, single-dose, dose-escalation phase I study to evaluate safety, tolerability, pharmacokinetics (PK), and cytokine responses after administration of recombinant TFF2-IFN proteins. Healthy volunteers were informed, enrolled, and randomized into four groups with a dose escalation of 0.2, 1, 2, and 4 mg and then inhaled the investigation product or placebo. Thirty-two eligible participants were finally enrolled; eight were assigned to the placebo group and 24 to the TFF2-IFN group, with six participants per group. Data were collected from 19 November 2021, to 4 January 2022. Results: All 32 participants completed the study. Of the participants who received the recombinant TFF2-IFN protein, 41.7% (10/24) reported 11 adverse events (AEs) during treatment and 62.5% (5/8) of those who received a placebo reported six AEs. Sixteen of the 17 AEs were grade 1. Only one grade 3 AE occurred in the placebo group and no worse event occurred as a serious adverse event. The pharmacokinetics was analyzed for times and concentrations of the investigation products in 0.2, 1, 2, and 4 mg groups in 24 recipients of TFF2-IFN, and the results showed that TFF2-IFN was retained in the lung for at least 6–8 h. Only the highest dose group (4 mg) had a transient detectable concentration in serum, while all other dose groups had a level below the lower limit of quantification. Conclusion: In this study, the recombinant TFF2-IFN protein was a well-tolerated and safe therapeutic when administered by nebulization, characterized by prolonged retention in the respiratory tract, which would be greatly beneficial in combating respiratory viral infection. Systematic Review Registration: [http://www.chictr.org.cn], identifier [ChiCTR2000035633].